Job Status, International Migration and Educational Choice - Ilhom Abdulloev; Gil S. Epstein; Ira N. Gang (Global Labor Organization (GLO), 2020)
We consider how the possibility of international migration affects an individual's educational choices in their home country. Without the opportunity to emigrate abroad people choose their educational investment (and hence their skill level) as we might expect, taking into account the utility they derive from the status their attainment bestows. A result of this paper is that if there are low chances of obtaining professional (requires tertiary schooling) jobs in the host country, individuals may well choose an educational track leading to a less-skilled lower status occupational profession in order to increase their chances of obtaining a job in the host country after migration. Thus, all home country students may choose the non-professional education track. Those who might have otherwise pursued higher, professional education may forgo that schooling. The theory developed here explains the forsaken schooling phenomenon, which shows that low-skilled and skilled home country workers are willing to accept low-skilled positions in host countries. This leads to the forgoing of professional schooling in the home country since it is not optimal for the worker in the home country to choose a high skilled education since, they will be overqualified in the host country. This will have a long run affect. As time goes on, therefore, people who consider migrating abroad will have either lower years of schooling, or generally have not completed professional schools (technical-vocational or tertiary).
Keywords: O15; P46; F22; I24; 330; traps; migration; poverty; inequality; education; skill; brain gain; brain drain